Recent Progress in Photoelectrochemical Water Splitting Activity of WO3 Photoanodes - Kalanur, Shankara S.; Duy, Le Thai; Seo, Hyungtak (Topics in Catalysis, 2018)
Photocatalytic and photoelectrochemical (PEC) water splitting to generate clean fuel H2 and O2 from water and solar energy using semiconductor nanomaterials is a green technology which could fulfill the growing energy need of the future and environment concerns. WOx≤3 has received considerable attention in photo-assisted water splitting due to its fascinating advantages such as absorbance in visible region up to ~ 480 nm, low cost, and stability in acidic and oxidative conditions. In this review, an attempt is made to summarize the important efforts made in the literature on the employment of WO3 for PEC water splitting in the last 5 years. Great milestones in PEC performance of WO3 have been reached with possible improvements via morphology control, crystal structure/facet, introduction of oxygen vacancy/defects and choice of suitable electrolyte. It is established that, WO3 nanostructure thin films require annealing, usually between 450 and 550 °C to attain more crystallinity and monoclinic phase of WOx≤3 is the most stable phase at room temperature and demonstrated highest photocatalytic activity when compared to other crystal phases. WO3 structures that are tightly interconnected and strongly bound to the metal collector substrate result in increased photogenerated charge collection efficiency while increase in PEC operating temperature augments the gas evolution quantity. Finally, we provide possibility for further improvements in WO3-based PCE which may be required to enhance its efficiency in water splitting.
Keywords: Crystal facets; Defect state; Nanostructure thin films; Photocatalytic activities; Photoelectrochemical water splitting; Photoelectrochemicals; Semiconductor nanomaterials; Tungsten substrate; Crystal facet; Crystal structure; Defect states; Electrolyte; Morphology; Photoelectrochemical water splitting; Tungsten substrate; WO3